Clinical and sociodemographic evaluation of peri-implant health of implant retained prostheses fabricated with an immediate oclusal loading protocol - CAPOROSSI,Leonardo Stephan (2019)
ABSTRACT Introduction Dental implant therapy, when well planned, can contribute to the patient's quality of life and is an important tool for solving a serious public health problem in various parts of the world. Objective This study investigated peri-implant health in fixed implants supported by an immediate loading technique and to associate those outcomes with sociodemographic conditions. Material and method After the disassembly of the prostheses on implants with the “Branemark Model” the peri-implant health of 93 patients was evaluated using dental plaque index (DPI), probing pocket depths (PPD), bleeding on probing (BOP), clinical attachment levels (CAL), and presence of gingival hyperplasia. Patients also answered a questionnaire about their gender, age, socioeconomic status (Brazilian Association of Research Companies - ABEP), general health and tobacco use. Result The most constant clinical findings were the presence of plaque, followed by gingival hyperplasia and periimplantitis, which was associated with disease progression. Most of the patients in the study were female, Caucasian, and under 60 years of age, with prostheses located in their lower arch, and they belonged to social classes A and B. Conclusion The presence of dental biofilm occurred in almost all implants and was not related to the presence of periimplantitis. The progression of periimplantitis with bone loss was related to sub gingival bleeding. The sociodemographic characteristics in the study did not present great correlations with the clinical variables of the dental implants studied.